Shape of image - Mohd Isa, Maryam; Zakaria, Nasir; Raid, Fadi Imad Osman Abu (Universiti Putra Malaysia Press, 2017)
An image represents or imitates the figure of the object. While the art of capturing image through a camera is common, duplicating an image with light is another interesting artform not as commonly explored. Image reflection in the darkness can be scary but sometimes interesting when the output of the object is represented in light.